2009
DOI: 10.1109/tie.2009.2029577
|View full text |Cite
|
Sign up to set email alerts
|

Static-, Dynamic-, and Mixed-Eccentricity Fault Diagnoses in Permanent-Magnet Synchronous Motors

Abstract: Mixed-eccentricity (ME) fault diagnosis has not been so far documented for permanent-magnet (PM) synchronous motors (PMSMs). This paper investigates how the static eccentricity (SE), dynamic eccentricity (DE), and ME in three-phase PMSMs can be detected. A novel index for noninvasive diagnosis of these eccentricities is introduced for a faulty PMSM. The nominated index is the amplitude of sideband components with a particular frequency pattern which is extracted from the spectrum of stator current. Using this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
156
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(157 citation statements)
references
References 26 publications
(16 reference statements)
0
156
0
1
Order By: Relevance
“…This change is observed as harmonics in the waveform of the induced current. Eccentricity fault in the PMSM is observed in the current and voltage spectrums as sideband components [3].…”
Section: Eccentricity Faults In Pmsmsmentioning
confidence: 99%
“…This change is observed as harmonics in the waveform of the induced current. Eccentricity fault in the PMSM is observed in the current and voltage spectrums as sideband components [3].…”
Section: Eccentricity Faults In Pmsmsmentioning
confidence: 99%
“…The former is much more common and includes three types: static, dynamic, and mixed eccentricity [13]. It has been concluded that stator current is the most commonly monitored signal for fault diagnosis because it is easily monitored without sensors [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, methods that rely only on the use of currents, like the Motor Current Signature Analysis (MCSA) [11], [12] are usually preferred mainly due to their non-invasive nature. The underlying philosophy of those methods is to detect the presence of specific components created by the fault.…”
Section: Introductionmentioning
confidence: 99%